Orquestra Errante, sixteen years of experimental practice in an academic environment: interview with Rogério Costa (Orfeu, 2025)
This interview with Prof. Dr. Rogério Costa, professor at Universidade de São Paulo and researcher in improvisation, discusses the experience of Orquestra Errante, organized by him since 2009. The group is focused on the practice of Free Improvisation and collective experimentation, sustaining itself through a particular informal, horizontal and self-managed organization. Our main focus here is the strategies for maintaining the group’s existence, in order to encourage reflection and discussion about possible resource for long-term sustainability of experimental projects in the Brazilian academic context, as well as the challenges faced by these projects.
Keywords: free improvisation; experimental practices; musical academy; collective creativity